Structural, optical and thermal properties of benzofluoran-based thermochromic composite - Hajzeri, Metka; Vatič, Nika; Panák, Ondrej; Kaplanová, Marie; Klanjšek Gunde, Marta (Univerzita Pardubice, 2013)
Thermochromic composites, consisting of leuco dye, colour developer and organic solvent indicate reversible thermochromism, with colouration in the solid state and discoloration in the molten state. These functional materials, the so-called smart materials, are of considerable interest in graphic art technology for applications such as temperature sensors, security markers, thermal printing, cutlery and clothing. Thermochromic composites of 6‘- (diethylamino)-1‘-2‘-benzofluoran (BF) dye, 2,2-bis(4-hydroxypheniyl) propane (BPA) developer and 1-octadecanol (OD) solvent were investigated in this work. Composites with four different molar ratios of BPA were analysed. The chemical structure, thermal and optical properties of samples were analysed by UV-VIS and FTIR spectroscopy, colorimetric measurements and differential scanning calorimetry. The applied methods enable to study the properties of the material below and above the phase-changes. Much interest was devoted to analyse how different molar ratio of developer influence on the structural, optical and thermal properties of the composites.
Keywords: thermochromic composites; leuco dye; structural; optical; thermal properties